PEMBELAJARAN MENYANYI LAGU DAERAH DITINJAU PADA ASPEK TEKNIK VOKAL DI KELAS VIII.4 SMP MUHAMMADIYAH 5 PADANG - Claudia Eka Putri; Robby Ferdian, Robby Ferdian (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the process of learning regional songs in class VIII.4 at SMP Muhammadiyah 5 Padang and to describe students' understanding of the basic aspects of vocal techniques taught. This research is a qualitative study with a descriptive method. The research instrument is the researcher themselves, assisted by writing tools and a camera. Data was collected through literature study, observation, interviews and documentation. The steps in analysing the data are data reduction, data presentation and drawing conclusions from the data. The results show that the process of learning regional songs in class VIII.4 at SMP Muhammadiyah 5 Padang, in terms of vocal techniques such as breathing, intonation, articulation, resonance and expression. Eighteen out of 25 students (72%) are still unable to properly control their breathing, causing their voice to often break when singing long phrases. In terms of intonation, 16 out of 25 students (64%) still produce inaccurate pitches, especially in parts of the melody with large interval jumps. Most students have never received specific vocal technique guidance in class, and the most dominant difficulties they face are in breathing and intonation. Although there is a gap between the ideal music learning and the actual conditions in the field, both teachers and students have a strong awareness and hope for improving the quality of learning. Teachers acknowledge the importance of vocal technique as a foundation for performing regional songs and express a desire to integrate vocal technique exercises more evenly in the future. Students also hope for more directed vocal technique guidance, especially before singing activities begin.